Membangun Budaya Digital Sehat: Edukasi Penggunaan Media Sosial Beretika Dan Berbasis Hukum - Nawwir Junari; Riska Herlena. S; Hendra Finur; Othman Ballan; Arga Chon Feriandref (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of Information Technology in recent years has been very rapid, including the development of social media. Almost all layers of society use social media, and in today's life, it is difficult to be separated from social media. However, this development does not match the understanding of healthy social media usage. Not a few, in fact many, members of society have encountered legal cases due to a lack of understanding of how to use social media. Some become victims and perpetrators without realizing it; some people become victims because they are not proficient in technology, while others become victims or even perpetrators due to not understanding the legal rules. This results in legal consequences that will have broad impacts, not only on the children and their families but also on the victims and society. This legal counseling collaborates knowledge of technology and legal understanding, so it is expected to provide understanding to all teenagers at SMA N 5 Batanghari. About Ethical and Law-Based Social Media Education. Providing understanding to students of SMA N 5 Batanghari about a healthy digital culture: healthy and law-based social media education and providing understanding of preventive measures to avoid becoming victims or perpetrators of criminal acts in the future.